Evaluation of Hypertension, Patient Tracking Card and Healthy Life Brochures Developed for Patient Education - Tokatlı Doğan, Merve; Erkaya Tosun, Müberra; Özkan, Seçil; Ekinci, Banu; Özkan Altunay, Zübeyde; Çobanoğlu, Nevin; Tamkoç Gürbüztürk, Fatma; Sis, Şükriye Seçil (Turkey Health Literacy Journal, 2021)
Objective: The aim of this study is to evaluate the Hypertension, Patient Tracking Card and Healthy Life brochures developed for patienteducationMethods: Face-to-face interview and questionnaire techniques were conducted to 64 patients who came to the outpatient clinics for examination, by introducing brochures developed for patient education them to read. The results of this descriptive study are presented in percentages. In addition, written recommendations were received for each brochure from experts who did not participate in developing the brochures.Results: Where all of the participants stated that the sentences were appealed to them, more than 80% of the participants expressed that there was no term they were not able to understand. The main topic was understood by almost all participants. All of the participants found the font and size of the text appropriate. All of the participants stated that item-by-item lists make it easier for them to read. They stated that there were no complicated charts and graphs. However, more than half of the participants thought that why “what to do”s are important was not explained adequately. They found the information given for blood pressure measurement, where to go for an appointment, and how to take their medications insufficient.Conclusion: As a result, attention was drawn to the importance of health education materials in patient education and its contribution tothe development of health literacy levels. The points to be considered while preparing effective health education material are included.
Keywords: Public health, health literacy; developing materials; visual materials; health education materials